Prevalence of depression in melasma: a systematic review and meta-analysis - Wenjing Chen; Wenjing Chen; Yue Wan; Yue Wan; Yuan Sun; Yuan Sun; Changyong Gao; Changyong Gao; Jianhong Li (Frontiers in Psychiatry, 2024)
BackgroundDue to cosmetic disfigurement, melasma can negatively affect the quality of life and emotional and mental health, further leading to depression.ObjectivePrevalence rates of depression in patients with melasma vary widely across studies. The aim of this systematic review and meta-analysis was to estimate the prevalence of depression among melasma patients.MethodsThe PubMed, Embase, Web of Science, and Scopus databases were searched to identify articles evaluating the prevalence of depression in melasma patients from their inception to 12 July 2023. Studies were reviewed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and a meta-analysis was performed using the Stata 14.0 software.ResultsSixteen studies met the eligibility criteria out of the 859 studies, containing a total of 2,963 melasma patients for this systematic review and meta-analysis. Meta-analyses revealed that the pooled prevalence of depression among patients with melasma was 43.4% (95% CI 30.5–56.2%, Q-value = 808.859, d.f. = 15, p < 0.001, tau2 = 0.065, I2 = 98.1%). The meta-regression found that the publication year, sample size, and study quality were not significant moderators for the observed heterogeneity in prevalence. A subgroup analysis according to depression assessment methods showed that the prevalence of depressive disorders was 24.2% (95% CI 16.8–31.6%), and the prevalence of depressive symptoms was 45.1% (95% CI 31.2–59.0%). A subgroup analysis by geographic regions showed that patients in Asia had the highest prevalence of depression at 48.5% (95% CI 26.0–71.0%), compared to other regions. A subgroup analysis by study design showed that the prevalence of depression in case–control studies was almost identical to cross-sectional studies. In the case of OR, the pooled OR of depression between patients with melasma and health controls was 1.677 (95% CI 1.163–2.420, p = 0.606, I2 = 0.0%).ConclusionThe prevalence of depression was relatively high in patients with melasma, and there was a correlation between melasma and depression, encouraging clinicians to screen for depression in their patients and providing a combination of physical and psychosocial support. If necessary, they should be referred to formal mental health services to seek professional psychological intervention.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42022381378.